Coexistence of Fabry Disease and Membranous Nephropathy (Iranian Journal of Kidney Diseases, 2016)
A 21-year-old man with no family history or characteristic symptoms of Fabry disease presented with proteinuria. Histological and immunofluorescent analysis of kidney tissue collected revealed stage 1 membranous nephropathy. Electron microscopy of the same tissue revealed a large number of myeloid bodies (zebra bodies) in the glomerular epithelial cytoplasm and a mild irregular thickening of basement membrane. A diagnosis of Fabry disease was supported by the low α-galactosidase A activity detected in the patient’s plasma, and confirmed by the detection of a pathogenic homozygous mutation in the α-galactosidase A gene. Therefore, the final diagnosis was of coexistent Fabry disease and stage 1 membranous nephropathy. This is the first case study reporting the coexistence of Fabry disease and membranous nephropathy. Our results emphasize the importance of electron microscopy in Fabry disease diagnosis.